2015
DOI: 10.1111/hepr.12596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum Wisteria floribunda agglutinin positive Mac‐2‐binding protein level and high‐sensitivity C‐reactive protein concentration in autoimmune hepatitis

Abstract: WFA(+) -M2BP can be a useful marker for assessing liver histological findings in AIH patients and it correlated well with hCRP concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
74
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 35 publications
10
74
3
1
Order By: Relevance
“…The range of the M2BPGi serum thresholds observed in chronic hepatitis C patientswas different from those described in primary biliary cirrhosis (PBC) or non-alcoholic fatty liver disease [14, 33], typeIautoimmune hepatitis [34], and hepatitis B (Matsumoto and Umemura, personal communications). This difference might be contributed to the difference in patients’ ethnicity or due to the fact that the majority of our cohort was asymptomatic and exhibited mild fibrosis.…”
Section: Discussionmentioning
confidence: 86%
“…The range of the M2BPGi serum thresholds observed in chronic hepatitis C patientswas different from those described in primary biliary cirrhosis (PBC) or non-alcoholic fatty liver disease [14, 33], typeIautoimmune hepatitis [34], and hepatitis B (Matsumoto and Umemura, personal communications). This difference might be contributed to the difference in patients’ ethnicity or due to the fact that the majority of our cohort was asymptomatic and exhibited mild fibrosis.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies also showed that WFA + ‐M2BP can be helpful for clinical outcome in HCC patients treated with surgical resection or in CHC patients treated with antiviral therapy . In addition, in our previous studies, we showed that WFA + ‐M2BP can be helpful for predicting the degree of liver fibrosis in patients with autoimmune hepatitis and primary biliary cirrhosis …”
Section: Introductionmentioning
confidence: 80%
“…It is interesting that patients with AIH had higher WFA + ‐M2BP concentrations than those with PSC alone. The presence of liver inflammation can cause higher WFA + ‐M2BP titers . Additionally, the multivariate analysis of this study shows that autoimmune hepatitis is only one significant predictor for the late histological group in PSC.…”
Section: Discussionmentioning
confidence: 58%